Non-linear Total Energy Optimisation of a Fleet of Power Plants - Nolle, Lars; Biegler-König, Friedrich; Deeskow, Peter (Applications and Innovations in Intelligent Systems XIV, 2006)
In order to optimise the energy production in a fleet of power plants, it is necessary to solve a mixed integer optimisation problem. Traditionally, the continuous parts of the problem are linearized and a Simplex scheme is applied. Alternatively, heuristic “bionic” optimisation methods can be used without having to linearize the problem. Weare going to demonstrate this approach by modelling power plant blocks with fast Neural Networks and optimising the operation of multi-block power plants over one day with Simulated Annealing.